(untitled) (Fourth World Journal, 2011)
This article analyzes the US government’s approach to the United Nations Declaration on the Rights of Indigenous Peoples, particularly the concept of ’free, prior and informed consent.’ It discusses the historical context, international obligations, and the shift towards ’government-to-government’ relations with Indian nations, highlighting challenges in implementation. It further delves into the nuances of government-to-government relations, emphasizing negotiations, protocols, and mutual agreements between the US and Indian governments. It explores the Trust Responsibility as a dynamic obligation and stresses the importance of mutual respect and communication. Last, it examines President Ronald Reagan’s 1983 American Indian policy statement, reaffirming the government-to-government relationship, tribal governance roles, and efforts to boost reservation economies, within the context of indigenous nations’ political development.